Sm-Nd isotopic constraints on the metadolerite dykes from Western Dharwar Craton, Southern India: implications on the evolution of Archean subcontinental lithospheric mantle - Silpa, A. S.; Satish-Kumar, M.; Takahashi, T.; Kamei, A. (Frontiers in Earth Science, 2023)
Metadolerite dykes in the Western Dharwar Craton represent the oldest generation of mafic dyke swarms in the craton. The emplacement of these dykes after a period of crust building activity and komatiite volcanism, helps to understand the evolution of Subcontinental Lithospheric Mantle (SCLM) and Archean dynamics. We report whole rock major, trace element geochemistry and Sr-Nd isotope characteristics for this weakly metamorphosed suite of dykes. Remnant igneous textures and mineralogy are well preserved. The trace and rare earth element concentrations and an overall flat pattern suggests depleted mantle source for these dykes. Three groups are primarily identified: Group 1 with initial 87Sr/86Sr ratios varying between 0.70041 to 0.70102, Group 2 dykes and Group 3 dykes with initial ratios 0.70045 to 0.70154, and 0.70041 to 0.70153 respectively. Group 1 dykes show a good Rb-Sr isochron relationship and an errorchron age of ca. 3003 ± 102 Ma is obtained. The initial 143Nd/144Nd ratios varies from 0.508245 to 0.509172. The epsilon Nd values are mostly negative, ranging between -12 to +5. Group 1 and 2 show an epsilon Nd value ranging between -1 to +5 and 0.1 to +5 respectively and group 3 varies between -0.5 and -12. The geochemical characteristics suggest that the group 1 dykes are derived from a homogenous depleted SCLM source, group 2 formed by a lower degree of partial melting of a source mantle with enriched components. Group 3 may have formed from a progressively enriched group 1 source. All these dykes can be considered as exposed remnants of feeders for the greenstone volcanism in the Western Dharwar Craton.